Effects of Health Belief Model-based Education on Maternal Abilities to Caring for Children With Avoidant Restrictive Food Intake Disorder - Yoyok Bekti Prasetyo; Yulis Setiya Dewi (Iran University of Medical Sciences, 2021)
Background: Health education, using new approaches in the nursing area, is of great importance. The current study aimed to evaluate the effects of a health belief model-based education on maternal abilities to caring for children with Avoidant Restrictive Food Intake Disorder (ARFID). Methods: This was a quasi-experimental non-randomized controlled trial with pre-test, post-test and a control group design. In total, 30 families with children with ARFID in Malang regency, Indonesia were divided into experimental and control groups. The experimental group was trained based on the Health Belief Model (HBM); however, the control group received an education based on the routine nursing process model. The necessary data were collected by a researcher-made questionnaire constructed based on HBM constructs. The obtained data were analyzed in SPSS. Descriptive statistics, homogeneity test, and Paired-Samples t-test were used to outline the relationship between the dependent and independent variables. Results: HBM effectively improved maternal abilities to manage eating disorders (P=0.009), promoting behaviors (P=0.000), and paternal involvement (P=0.000). Conclusion: HBM-Based education is recommended to be used in the provision of training in the mothers of children with ARFID.